Method for manufacturing laminate, and laminate
Patent Information
- Application Number
- JP2023127148
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-03
- Publication Date
- 2025-02-14
AI Technical Summary
【0018】 本発明によれば、外観に優れた積層体を得ることができる。
Smart Images

Figure 2025022504000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a method for producing a laminate and the laminate. [Background technology]
[0002] As part of efforts to address the environmental issues, flexible packaging bags using plastic films are becoming more and more popular as a replacement for bottles and cans. In many cases, flexible packaging bags are made of a laminate of two or more films bonded together with an adhesive to improve their performance, such as strength, water resistance, moisture resistance, gas barrier properties including oxygen, and heat resistance.
[0003] Furthermore, adhesives used to bond laminates are increasingly being replaced with solvent-free adhesives (see, for example, Patent Document 1). Solvent-free adhesives do not use solvents during coating, so they can reduce the thermal energy required for the drying process after coating and air pollution caused by volatile organic compounds (VOCs), making it possible to reduce the burden on the environment. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2010-280122 A Summary of the Invention [Problem to be solved by the invention]
[0005] Laminates using solvent-free adhesives for bonding have a problem of poor appearance due to the formation of air bubbles in the adhesive layer, which is particularly noticeable when films with high gas barrier properties are bonded to the laminate.
[0006] In order to improve this poor appearance, for example, Patent Document 1 states that by providing a dry coating layer of a coating resin on the film and then applying a solvent-free adhesive on top of that, it is possible to increase the adhesion between the film and the adhesive when laminating them, thereby improving the poor appearance. However, the method described in Patent Document 1 requires additional coating and drying processes of the coating resin, which poses the problem of compromising the effect of reducing environmental impact, which is an advantage of solvent-free adhesives.
[0007] The present invention has been made to solve such problems, and an object of the present invention is to provide a method for producing a laminate that can produce a laminate with excellent appearance, and a laminate with excellent appearance. [Means for solving the problem]
[0008] The present inventors conducted extensive research to solve the above problems, and discovered the following. That is, when the laminate is wound into a roll in the lamination process, the laminate is pressed toward the radial center of the winding roll due to the tightening of the laminate. At this time, the inventors discovered that the step of the printed layer causes a difference in pressure generated in the laminate, and that the collection of air bubbles generated in the adhesive layer is affected by this pressure difference. Therefore, the inventors discovered that by performing the printing process after the lamination process, the difference in pressure generated by the tightening of the laminate can be reduced, and thus large air bubbles are not generated in the adhesive layer, improving the appearance, and completed the present invention. That is, the present invention provides the following [1] to [5].
[0009] [1] A method for manufacturing a laminate, comprising: a lamination step in which a first film and a second film are bonded together with a solvent-free adhesive to obtain a first laminate in which a first film, a first adhesive layer made of a solvent-free adhesive, and a second film are laminated in that order; and a printing step in which, after the lamination step, a printed layer is formed on the surface of the first film opposite the second film.
[0010] In this laminate manufacturing method, a laminate in which a printed layer, a first film, a first adhesive layer made of a solventless adhesive, and a second film are laminated in this order can be obtained by performing a lamination process and a printing process. Here, when the first laminate is wound into a roll in the lamination process, the first laminate is compressed toward the radial center of the winding roll due to the tightening of the first laminate. At this time, by performing the lamination process before the printing process, the first laminate wound into a roll does not have a printed layer formed on the first film, so that the pressure distribution between the first film and the second film is more uniform than when the lamination process is performed after the printing process. This makes it possible to suppress the flow of air bubbles contained in the first adhesive layer between the first film and the second film, and thus to obtain a laminate with improved appearance by suppressing the formation of air bubbles in the first adhesive layer.
[0011] [2] The method for producing the laminate described in [1] further includes a second lamination step in which, after the printing step, a third film is adhered to the surface of the second film opposite the first film with a solvent-free adhesive to obtain a second laminate in which the printed layer, the first film, the first adhesive layer, the second film, a second adhesive layer made of a solvent-free adhesive, and the third film are laminated in this order, and then the second laminate is wound up into a roll.
[0012] In this method for producing a laminate, a laminate can be obtained by performing a second lamination step, in which a printed layer, a first film, a first adhesive layer, a second film, a second adhesive layer made of a solventless adhesive, and a third film are laminated in this order. Here, since the second lamination step is performed after the printing step, the second laminate wound into a roll has a printed layer formed on the first film. However, since the second laminate wound into a roll has a thickness greater than that of the first laminate wound into a roll in the lamination step, the influence of the printed layer on the pressure distribution between the second film and the third film is reduced. Therefore, a laminate with improved appearance can be obtained by suppressing the formation of air bubbles in the second adhesive layer.
[0013] [3] A laminate comprising a first film, a second film, a first adhesive layer disposed between the first film and the second film, and a printed layer formed on the surface of the first film opposite the second film, wherein the first adhesive layer is made of a solvent-free adhesive and does not have any air bubbles having a diameter of 0.1 mm or more.
[0014] In this laminate, the first adhesive layer is made of a solvent-free adhesive and does not contain air bubbles with a diameter of 0.1 mm or more, thereby improving the appearance while minimizing the burden on the environment.[4] The laminate described in [3], wherein the oxygen permeability of the first film and the second film is 20 cc / day·atm or less.
[0015] In this laminate, the oxygen permeability of the first and second films is 20 cc / day·atm or less, so air bubbles are unlikely to permeate through the first and second films. However, by using the above-mentioned method for producing a laminate, the first adhesive layer can be made free of air bubbles with a diameter of 0.1 mm or more, improving the appearance.
[0016] [5] The laminate described in [3] or [4], further comprising a third film arranged on the opposite side of the second film from the first film, and a second adhesive layer arranged between the second film and the third film, wherein the second adhesive layer is made of a solvent-free adhesive and does not have any air bubbles having a diameter of 0.1 mm or more.
[0017] In this laminate, the second adhesive layer is made of a solvent-free adhesive, but does not contain air bubbles with a diameter of 0.1 mm or more, thereby improving the appearance while minimizing the burden on the environment. Effect of the Invention
[0018] According to the present invention, a laminate having excellent appearance can be obtained. [Brief description of the drawings]
[0019] [Figure 1]FIG. 1 is a schematic cross-sectional view showing a laminate according to the first embodiment. [Diagram 2] FIG. 2 is a flowchart showing the method for producing a laminate according to the first embodiment. [Diagram 3] FIG. 3 is a schematic cross-sectional view for explaining lamination in the lamination step. [Figure 4] FIG. 4 is a schematic diagram for explaining the winding in the lamination process. [Diagram 5] FIG. 5 is a schematic cross-sectional view for explaining the printing process. [Figure 6] FIG. 6 is a schematic cross-sectional view showing a laminate of a comparative example. [Figure 7] FIG. 7 is a flowchart showing a method for producing a laminate of the comparative example. [Figure 8] FIG. 8 is a schematic cross-sectional view showing a laminate according to the second embodiment. [Figure 9] FIG. 9 is a flowchart showing a method for producing a laminate according to the second embodiment. [Figure 10] FIG. 10 is a schematic cross-sectional view for explaining lamination in the second lamination step. [Figure 11] FIG. 11 is a schematic diagram for explaining the winding in the second lamination step. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] Hereinafter, an embodiment of the present invention will be described in detail with reference to the drawings. In the following description, the same or corresponding elements are designated by the same reference numerals, and duplicated description will be omitted.
[0021] [First embodiment] (Laminate) Fig. 1 is a schematic cross-sectional view showing a laminate according to a first embodiment. As shown in Fig. 1, a laminate 1 according to the first embodiment includes a printed layer 2, a first film 3, a first adhesive layer 4, and a second film 5. In this laminate 1, the printed layer 2, the first film 3, the first adhesive layer 4, and the second film 5 are laminated in this order.
[0022] The printing layer 2 is formed on the surface 3a of the first film 3 opposite to the second film 5. The printing layer 2 is an ink layer formed of one or more inks. For example, general gravure ink, flexo ink, offset ink, and digital printing ink can be used as the printing layer 2. Among them, inks suitable for surface printing, such as PANNECO (manufactured by Toyo Ink Co., Ltd.), Real NEX BO S3 (manufactured by Toyo Ink Co., Ltd.), and Ultima NT (manufactured by DIC Graphics Co., Ltd.), are preferable. When the color ink is an oil-based gravure ink, the binder resin may be a mixture of urethane resin and vinyl chloride-vinyl acetate copolymer resin. The color ink may contain various additives other than the pigment and binder resin, and a solvent (for example, a volatile organic solvent). For example, vegetable oil ink, biomass ink, and the like can also be used as the color ink. The thickness of the printing layer 2 is, for example, 0.2 m or more and 8 μm or less. The thickness of the printed layer 2 is equal to the height of the step between the first film 3 and the printed layer 2 .
[0023] The first film 3 is a film on which the printed layer 2 is formed. As the first film 3, for example, a film made of at least one of polyesters such as polyethylene terephthalate, polyethylene naphthalate, and polybutylene terephthalate, polyamides such as nylon, polypropylene, polystyrene, polyethylene, polyimide, polyvinyl alcohol, polyvinyl chloride, and ethylene-vinyl alcohol copolymers, or a composite film formed by laminating two or more of these films can be used. The first film 3 may include a barrier layer such as an aluminum foil, a metal deposition layer, or a transparent deposition layer of an inorganic oxide (deposition layer of an inorganic oxide). Depending on the application, the first film 3 may also include other functional layers such as a concealment layer. The thickness of the first film 3 is, for example, 10 μm or more and 100 μm or less. The oxygen permeability of the first film 3 is, for example, 20 cc / day·atm or less.
[0024] The first adhesive layer 4 bonds the first film 3 and the second film 5. The first adhesive layer 4 is a layer made of a solvent-free adhesive 4a, and is, for example, a layer formed by hardening the solvent-free adhesive 4a. The solvent-free adhesive 4a is an adhesive that does not contain an organic solvent. The fact that the adhesive layer is formed using a solvent-free adhesive rather than a solvent-based adhesive can be analyzed, for example, by Fourier transform infrared spectroscopy. Examples of the solvent-free adhesive 4a include two-component curing polyurethane adhesives in which an aromatic or aliphatic isocyanate compound having two or more functional groups is allowed to act on a base agent such as polyester polyol, polyether polyol, or acrylic polyol as a curing agent. In such adhesives, the components react with each other by heating or the like (for example, the hydroxyl group of the base agent reacts with the isocyanate group of the curing agent) to harden the adhesive layer, forming the adhesive layer. That is, the adhesive layer may be a (reaction) hardened product of a two-component curing polyurethane adhesive, which is a solvent-free adhesive.
[0025] The thickness of the first adhesive layer 4 is, for example, 0.3 μm or more and 5.0 μm or less. The first adhesive layer 4 does not have bubbles with a diameter of 0.1 mm or more. The first adhesive layer 4 does not have bubbles with a diameter of 0.1 mm or more by producing the laminate 1 by the laminate producing method described below. The first adhesive layer 4 may have bubbles with a diameter of less than 0.1 mm. When the bubbles are not spherical, the diameter of the bubbles refers to the maximum diameter of the bubbles.
[0026] The second film 5 is a film disposed on the opposite side of the first film 3 from the printed layer 2, and is bonded to the first film 3 by the first adhesive layer 4. As the second film 5, a film similar to that of the first film 3 can be used, for example, a film made of at least one of polyesters such as polyethylene terephthalate, polyethylene naphthalate, and polybutylene terephthalate, polyamides such as nylon, polypropylene, polystyrene, polyethylene, polyimide, polyvinyl alcohol, polyvinyl chloride, and ethylene-vinyl alcohol copolymers, a metal foil such as aluminum foil, and a composite film formed by laminating two or more of these films. However, when the second film 5 is used as a sealant layer, a non-oriented polypropylene film, a non-oriented polyethylene film, and the like are particularly used. The thickness of the second film 5 is, for example, 3 μm or more and 150 μm or less. The oxygen permeability of the second film 5 is, for example, 20 cc / day·atm or less.
[0027] (Method of manufacturing laminate) Next, a method for producing the laminate according to the first embodiment will be described. The method for producing the laminate according to the first embodiment is a method for producing the laminate 1 described above.
[0028] Fig. 2 is a flow chart showing a method for producing a laminate according to the first embodiment. As shown in Fig. 2, in the method for producing a laminate according to the first embodiment, a laminating step (S1) and a printing step (S2) are performed in this order. In the laminating step (S1), lamination is performed, and then winding is performed.
[0029] Fig. 3 is a schematic cross-sectional view for explaining lamination in the lamination step. As shown in Fig. 3, in the lamination step (S1), first, a first film 3 and a second film 5 are bonded with a solventless adhesive 4a as lamination. This results in a first laminate 1a in which the first film 3, the first adhesive layer 4 made of the solventless adhesive 4a, and the second film 5 are laminated in this order.
[0030] FIG. 4 is a schematic diagram for explaining the winding in the lamination step. As shown in FIG. 3 and FIG. 4, in the lamination step (S1), the first laminate 1a is then wound into a roll. The first laminate 1a wound into a roll is called a roll 10. At this time, the first laminate 1a is compressed toward the center of the roll 10 in the radial direction due to the tightening of the winding. That is, the first film 3 and the second film 5 are compressed in a direction in which they approach each other. Then, the roll 10 is aged until the first adhesive layer 4 is cured. The aging is performed, for example, by storing the roll 10 in a storage cabinet at 40° C. for two days.
[0031] Fig. 5 is a schematic cross-sectional view for explaining the printing step. As shown in Fig. 3 and Fig. 5, in the printing step (S2), the first laminate 1a is pulled out from the roll 10, and a printed layer 2 is formed on the surface 3a of the first film 3 opposite to the second film 5. This results in a laminate 1 in which the printed layer 2, the first film 3, the first adhesive layer 4, and the second film 5 are laminated in this order. From the viewpoint of ease of transport and storage of the laminate 1, the laminate 1 is often wound up into a roll after the printing step (S2).
[0032] Here, a laminate of a comparative example and a method for manufacturing the laminate will be described with reference to FIGS.
[0033] Fig. 6 is a schematic cross-sectional view showing a laminate of a comparative example. As shown in Fig. 6, the laminate 101 of the comparative example is formed by laminating a first film 103, a printed layer 102, a first adhesive layer 104 made of a solvent-free adhesive 104a, and a second film 105 in this order. That is, the printed layer 102 is formed on a surface 103b of the first film 103 facing the second film 105, and the second film 105 is bonded to the surface 103b of the first film 103 facing the printed layer 102 with the solvent-free adhesive 104a.
[0034] FIG. 7 is a flow chart showing a method for manufacturing a laminate of a comparative example. As shown in FIG. 7, in the method for manufacturing a laminate of a comparative example, a printing step (S101) and a laminating step (S102) are performed in this order. In the printing step (S101), a printed layer 102 is formed on one surface 103b of a first film 103. In the laminating step (S102), a second film 105 is first adhered to the surface 103b of the first film 103 on the printed layer 102 side with a solvent-free adhesive 104a to obtain a laminate 101 in which the first film 103, the printed layer 102, the first adhesive layer 104 made of the solvent-free adhesive 104a, and the second film 105 are laminated in this order. In the laminating step (S102), the laminate 101 is then wound into a roll. Then, the rolled laminate 101 is aged until the first adhesive layer 104 is cured.
[0035] As described above, in the laminate manufacturing method of the comparative example, the lamination step (S102) is performed after the printing step (S101), so that the laminate 101 wound into a roll has the printed layer 102 formed on the first film 103. Therefore, in the laminate 101 wound into a roll, the printed layer 102 forms a step, and a large pressure difference occurs between the portion where the printed layer 102 is formed and the portion where the printed layer 102 is not formed. This makes it easier for air bubbles contained in the first adhesive layer 104 to flow between the first film 103 and the second film 105, so that the air bubbles gather in the first adhesive layer 104 and increase in diameter, which makes it easier for poor appearance to occur.
[0036] In contrast, in the laminate manufacturing method according to the present embodiment, by performing the laminating step (S1) before the printing step (S2), the roll 10 of the first laminate 1a wound into a roll does not have the printed layer 2 formed on the first film 3, and therefore the pressure distribution between the first film 3 and the second film 5 is more uniform than in the comparative example in which the laminating step (S102) is performed after the printing step (S101). This makes it possible to suppress air bubbles contained in the first adhesive layer 4 from flowing between the first film 3 and the second film 5, thereby making it possible to obtain a laminate 1 with improved appearance by suppressing the formation of air bubble collection in the first adhesive layer 4.
[0037] In the laminate 1 of this embodiment, the first adhesive layer 4 is made of a solvent-free adhesive 4a, and does not contain air bubbles with a diameter of 0.1 mm or more, thereby improving the appearance while minimizing the burden on the environment.
[0038] Furthermore, in the laminate 1 according to this embodiment, the first film 3 and the second film 5 have an oxygen permeability of 20 cc / day·atm or less, and therefore air bubbles are unlikely to permeate through the first film 3 and the second film 5. However, by using the above-described method for producing a laminate, the first adhesive layer 4 can be made free of air bubbles with a diameter of 0.1 mm or more, and therefore the appearance is improved.
[0039] [Second embodiment] (Laminate) Fig. 8 is a schematic cross-sectional view showing a laminate according to the second embodiment. As shown in Fig. 8, the laminate 1A according to the second embodiment includes a printed layer 2, a first film 3, a first adhesive layer 4, a second film 5, a second adhesive layer 6, and a third film 7. In this laminate 1, the printed layer 2, the first film 3, the first adhesive layer 4, the second film 5, the second adhesive layer 6, and the third film 7 are laminated in this order. The printed layer 2, the first film 3, the first adhesive layer 4, and the second film 5 can be the same as those of the laminate 1 according to the first embodiment.
[0040] The second adhesive layer 6 bonds the second film 5 and the third film 7. The second adhesive layer 6 is a layer made of a solvent-free adhesive 6a, and is, for example, a layer formed by hardening the solvent-free adhesive 6a. The solvent-free adhesive 6a constituting the second adhesive layer 6 can be, for example, the same as the solvent-free adhesive 4a constituting the first adhesive layer 4. The thickness of the second adhesive layer 6 is, for example, 0.3 μm or more and 5.0 μm or less. The second adhesive layer 6 does not have bubbles with a diameter of 0.1 mm or more. The second adhesive layer 6 does not have bubbles with a diameter of 0.1 mm or more by manufacturing the laminate 1A by the laminate manufacturing method described later. The second adhesive layer 6 may have bubbles with a diameter of less than 0.1 mm. When the bubbles are not spherical, the diameter of the bubbles refers to the maximum diameter of the bubbles.
[0041] The third film 7 is a film disposed on the opposite side of the second film 5 to the first film 3 and bonded to the second film 5 by the second adhesive layer 6. As the third film 7, a film similar to the first film 3 can be used, for example, a film made of at least one of polyesters such as polyethylene terephthalate, polyethylene naphthalate, and polybutylene terephthalate, polyamides such as nylon, polypropylene, polystyrene, polyethylene, polyimide, polyvinyl alcohol, polyvinyl chloride, and ethylene-vinyl alcohol copolymers, or a composite film formed by laminating two or more of these films, but when used as a sealant layer, a non-stretched polypropylene film, a non-stretched polyethylene film, or the like is often used. The thickness of the third film 7 is, for example, 3 μm or more and 150 μm or less. It is preferable that the oxygen permeability of at least one of the first film 3, the second film 5, and the third film 7 is 20 cc / day·atm or less.
[0042] (Method of manufacturing laminate) Next, a description will be given of a method for producing a laminate according to the second embodiment. The method for producing a laminate according to the second embodiment is a method for producing the above-mentioned laminate 1A.
[0043] Fig. 9 is a flow chart showing a method for manufacturing a laminate according to the second embodiment. As shown in Fig. 9, in the method for manufacturing a laminate according to the first embodiment, a lamination step (S1), a printing step (S2), and a second lamination step (S3) are performed in this order. The lamination step (S1) and the printing step (S2) can be the same as those in the method for manufacturing a laminate according to the first embodiment. In the second lamination step (S3), lamination is performed, and then winding is performed.
[0044] Fig. 10 is a schematic cross-sectional view for explaining lamination in the second lamination step. As shown in Fig. 5 and Fig. 10, in the second lamination step (S3), first, as lamination, a third film 7 is adhered to the surface 5a of the second film 5 opposite to the first film 3 with a solvent-free adhesive 6a. This results in a second laminate 1Aa in which the printed layer 2, the first film 3, the first adhesive layer 4, the second film 5, the second adhesive layer 6 made of the solvent-free adhesive 6a, and the third film 7 are laminated in this order.
[0045] FIG. 11 is a schematic diagram for explaining the winding in the second lamination step. As shown in FIG. 10 and FIG. 11, in the second lamination step (S3), the second laminate 1Aa is then wound into a roll. The second laminate 1Aa wound into a roll is called a roll 10A. At this time, the second laminate 1Aa is compressed toward the radial center of the roll 10A due to the tightening of the winding of the second laminate 1Aa. That is, the second film 5 and the third film 7 are compressed in a direction in which they approach each other. Then, the roll 10A is aged until the second adhesive layer 6 is cured. The aging is performed, for example, by storing it in a storage at 40°C for two days. As a result, a laminate 1A is obtained in which the printing layer 2, the first film 3, the first adhesive layer 4, the second film 5, the second adhesive layer 6, and the third film 7 are laminated in this order.
[0046] Here, in the laminate manufacturing method according to this embodiment, since the second lamination step (S3) is performed after the printing step (S2), the roll 10A of the second laminate 1Aa wound into a roll has the printed layer 2 formed on the first film 3. However, since the second laminate 1Aa wound into a roll has a thickness greater than that of the first laminate 1a wound into a roll in the lamination step (S1), the influence of the printed layer 2 on the pressure distribution between the second film 5 and the third film 7 is reduced. For this reason, it is possible to obtain a laminate 1A having an improved appearance by suppressing the formation of air bubbles in the second adhesive layer 6.
[0047] Furthermore, in the laminate 1A of this embodiment, the second adhesive layer 6 is made of a solvent-free adhesive 6a, and does not contain air bubbles having a diameter of 0.1 mm or more, thereby improving the appearance while minimizing the burden on the environment.
[0048] Although an embodiment of the present invention has been described above, the present invention is not limited to the above embodiment, and may be modified or applied to other things without departing from the gist of the claims. EXAMPLES
[0049] The present invention will be described in more detail with reference to the following examples, but the present invention is not limited to these examples.
[0050] Comparative Example 1 In Comparative Example 1, a printed PET film "E5102" (12 μm thick, manufactured by Toyobo Co., Ltd.) and a VM-CPP film "2203" (25 μm thick, oxygen permeability 10 cc / m, manufactured by Toray Advanced Film Co., Ltd.) were used. 2 The above materials were laminated in this order to obtain a laminate.
[0051] The printed PET film "E5102" used had a printed layer already formed on the laminated surface of the PET film "E5102" by gravure printing. The color ink used was "Riogran R651 White" manufactured by Toyo Ink Co., Ltd. The printed pattern was two 3μm-thick stripes uniformly distributed across the width of the film at a width of 50mm, running parallel to each other in the flow direction with a gap of 100mm between them.
[0052] For lamination, a solvent-free adhesive "LOCTITE LIOFOL LA7795 / 6204" (manufactured by Henkel Japan Ltd.) was used, mixed in a weight ratio of 100:80, and applied with a roll coater at a rate of 2.0 g / m. 2 The laminate was wound into a roll and aged at 40°C for 2 days.
[0053] Comparative Example 2 In Comparative Example 2, a printed Ny film "ONMB-RT" (15 μm thick, manufactured by Unitika Ltd.) and a VM-PET film "1510" (12 μm thick, oxygen permeability 0.7 cc / m, manufactured by Toray Advanced Film Co., Ltd.) were used. 2 100 μm thick) and an LLDPE film “LC-2T” (manufactured by Tamapoly Corporation) were laminated in this order to obtain a laminate.
[0054] The printed Ny film "ONMB-RT" used had a printed layer formed on the laminated surface of the Ny film "ONMB-RT" by gravure printing. The color ink used was "Riogran R651 White" manufactured by Toyo Ink Co., Ltd. The printed pattern was two 3μm-thick stripes that were uniformly distributed across the width of the film at a width of 50mm, and continued in parallel in the flow direction with a gap of 100mm between them.
[0055] For lamination, a solvent-free adhesive "LOCTITE LIOFOL LA7795 / 6204" (manufactured by Henkel Japan Ltd.) was used, mixed in a weight ratio of 100:80, and applied with a roll coater at a rate of 2.0 g / m. 2The laminated film was wound into a roll and aged at 40°C for 2 days.
[0056] Comparative Example 3 In Comparative Example 3, a printed transparent barrier PET film "GL-ARH" (manufactured by Toppan Printing Co., Ltd., 12 μm thick, oxygen permeability 0.2 cc / m 2 A laminate was obtained by laminating a 15-μm-thick Ny film “ONMB-RT” (manufactured by Unitika Ltd.), a 15 μm-thick Ny film “ONMB-RT”, and a 60 μm-thick CPP film “ZK 207” (manufactured by Toray Advanced Film Co., Ltd.) in this order.
[0057] The printed transparent barrier PET film "GL-ARH" used had a printed layer already applied by gravure printing to the laminated surface of the transparent barrier PET film "GL-ARH." The color ink used was "Riogran R651 White" manufactured by Toyo Ink Co., Ltd. The printed pattern was two 3μm-thick stripes that were uniformly distributed across the width of the film at a width of 50mm, running parallel to each other in the flow direction with a gap of 100mm between them.
[0058] For lamination, a solvent-free adhesive "LOCTITE LIOFOL LA7795 / 6204" (manufactured by Henkel Japan Ltd.) was used, mixed in a weight ratio of 100:80, and applied with a roll coater at a rate of 2.0 g / m. 2 The laminated film was wound into a roll and aged at 40°C for 2 days.
[0059] Comparative Example 4 In Comparative Example 4, a printed transparent barrier PET film "GL-ARH" (manufactured by Toppan Printing Co., Ltd., 12 μm thick, oxygen permeability 0.2 cc / m 2 A laminate was obtained by laminating a 15-μm-thick Ny film “ONMB-RT” (manufactured by Unitika Ltd.), a 15 μm-thick Ny film “ONMB-RT”, and a 60 μm-thick CPP film “ZK 207” (manufactured by Toray Advanced Film Co., Ltd.) in this order.
[0060] The printed transparent barrier PET film "GL-ARH" was a transparent barrier PET film "GL-ARH" with a printed layer already applied by gravure printing on the side opposite to the side to which the adhesive was applied. The color ink used was "PANNECO AM630 White" manufactured by Toyo Ink Co., Ltd. The printed pattern was two 3μm-thick band-shaped patterns uniformly distributed across the width of the film at a width of 50mm, running parallel to each other in the flow direction with a gap of 100mm between them.
[0061] For lamination, a solvent-free adhesive "LOCTITE LIOFOL LA7795 / 6204" (manufactured by Henkel Japan Ltd.) was used, mixed in a weight ratio of 100:80, and applied with a roll coater at a rate of 2.0 g / m. 2 The laminated film was wound into a roll and aged at 40°C for 2 days.
[0062] Example 1 In Example 1, the printed PET film "E5102" was replaced with an unprinted PET film "E5102" for lamination processing, and after aging, a printing layer was formed by gravure printing on the side of the PET film "E5102" opposite the VM-CPP film "2203" using "PANNECO AM630 white" manufactured by Toyo Ink Co., Ltd., except for this, processing was carried out in the same manner as in Comparative Example 1.
[0063] Example 2 In Example 2, Ny film "ONMB-RT" (15 μm thick, manufactured by Unitika Ltd.) and VM-PET film "1510" (12 μm thick, oxygen permeability 0.7 cc / m, manufactured by Toray Advanced Film Co., Ltd.) were used. 2 The laminated laminate was wound into a roll and aged at 40°C for 2 days.
[0064] After aging, a printed layer was applied by gravure printing to the side of the Ny film "ONMB-RT" opposite the VM-PET film "1510". The color ink used was "PANNECO AM630 White" manufactured by Toyo Ink Co., Ltd. The printed pattern was two 3μm-thick stripes that were uniformly distributed across the width of the film at a width of 50mm, and continued parallel to each other in the flow direction with a gap of 100mm between them.
[0065] After printing, the LLDPE film "LC-2T" (50 μm thick, manufactured by Tamapoly Co., Ltd.) was laminated to the opposite side of the VM-PET film "1510" from the Ny film "ONMB-RT".
[0066] For lamination, a solvent-free adhesive "LOCTITE LIOFOL LA7795 / 6204" (manufactured by Henkel Japan Ltd.) was used, mixed in a weight ratio of 100:80, and applied with a roll coater at a rate of 2.0 g / m. 2 The laminate was wound into a roll and aged at 40°C for 2 days.
[0067] Example 3 In Example 3, a transparent barrier PET film "GL-ARH" (manufactured by Toppan Printing Co., Ltd., 12 μm thick, oxygen permeability 0.2 cc / m 2 A laminate was obtained by laminating a 100-μm-thick Ny film "ONMB-RT" (15 μm-thick, manufactured by Unitika Ltd.) in this order. The laminate was wound into a roll and aged at 40° C. for 2 days.
[0068] After aging, a printing layer was applied by gravure printing to the side of the transparent barrier PET film "GL-ARH" opposite the Ny film "ONMB-RT". The color ink used was "PANNECO AM630 White" manufactured by Toyo Ink Co., Ltd. The printed pattern was two 3μm-thick stripes uniformly distributed across the width of the film at a width of 50mm, running parallel to each other in the flow direction with a gap of 100mm between them.
[0069] After printing, the CPP film “ZK 207” (60 μm thick, manufactured by Toray Advanced Film Co., Ltd.) was laminated to the opposite side of the Ny film “ONMB-RT” of the laminate to the transparent barrier PET film “GL-ARH”.
[0070] For lamination, a solvent-free adhesive "LOCTITE LIOFOL LA7795 / 6204" (manufactured by Henkel Japan Ltd.) was used, mixed in a weight ratio of 100:80, and applied with a roll coater at a rate of 2.0 g / m. 2 The laminate was wound into a roll and aged at 40°C for 2 days.
[0071] (evaluation) For the laminates of Comparative Examples 1 to 4 and Examples 1 to 3, the unprinted parts between the printed layers were observed over a distance of 1 m in the machine direction, and the appearance was evaluated using the following indices. The evaluation results are shown in Table 1. A: There are no air bubbles with a diameter of 0.1 mm or more. B: Bubbles with a diameter of 0.1 mm or more and less than 0.5 mm are present. C: Bubbles with a diameter of 0.5 mm or more and less than 1 mm are present. D: Bubbles with a diameter of 1 mm or more are present.
[0072] [Table 1]
[0073] As shown in Table 1, Comparative Examples 1 to 4, in which lamination was performed after printing, were rated as B to D in appearance, whereas Examples 1 to 3, in which lamination was performed before printing, were all rated as A in appearance. From this result, it was found that by performing lamination after printing, it is possible to obtain a laminate with improved appearance by suppressing the formation of air bubbles in the adhesive layer. In addition, it was found that even if lamination was performed after printing, it is possible to obtain a laminate with improved appearance by suppressing the formation of air bubbles in the adhesive layer by performing lamination before printing. [Explanation of symbols]
[0074] 1...laminate, 1a...first laminate, 1A...laminate, 1Aa...second laminate, 2...printed layer, 3...first film, 3a...surface, 4...first adhesive layer, 4a...solvent-free adhesive, 5...second film, 5a...surface, 6...second adhesive layer, 6a...solvent-free adhesive, 7...third film, 10...roll, 10A...roll, 101...laminate, 102...printed layer, 103...first film, 103b...surface, 104...first adhesive layer, 104a...solvent-free adhesive, 105...second film.
Claims
1. a lamination step of bonding a first film and a second film with a solvent-free adhesive to obtain a first laminate in which the first film, a first adhesive layer made of the solvent-free adhesive, and the second film are laminated in this order, and then winding up the first laminate into a roll; A printing step of forming a printed layer on a surface of the first film opposite to the second film after the laminating step. A method for manufacturing a laminate.
2. the method further includes a second lamination step of, after the printing step, adhering a third film to a surface of the second film opposite to the first film with a solvent-free adhesive to obtain a second laminate in which a printing layer, the first film, the first adhesive layer, the second film, a second adhesive layer made of the solvent-free adhesive, and a third film are laminated in this order, and then winding up the second laminate into a roll. A method for producing the laminate according to claim 1 .
3. The first film, The second film, a first adhesive layer disposed between the first film and the second film; a printed layer formed on a surface of the first film opposite to the second film, The first adhesive layer is made of a solvent-free adhesive and does not have air bubbles having a diameter of 0.1 mm or more. Laminate.
4. The oxygen permeability of the first film and the second film is 20 cc / day atm or less. The laminate according to claim 3.
5. a third film disposed on an opposite side of the second film from the first film; a second adhesive layer disposed between the second film and the third film, The second adhesive layer is made of a solvent-free adhesive and does not have air bubbles having a diameter of 0.1 mm or more. The laminate according to claim 3 or 4.
Citation Information
Patent Citations
JP280122A